Optimized genotyping method for identification of bacterial contaminants in pharmaceutical industry - Stamatoski Borche; Ilievska Miroslava; Babunovska Hristina; Sekulovski Nikola; Panov Sasho (Acta Pharmaceutica)
Microbiological control is of crucial importance in the pharmaceutical industry regarding the possible bacterial contamination of the environment, water, raw materials and finished products. Molecular identification of bacterial contaminants based on DNA sequencing of the hypervariable 16SrRNA gene has been introduced recently. The aim of this study is to investigate the suitability of gene sequencing using our selection of PCR primers and conditions for rapid and accurate bacterial identification in pharmaceutical industry quality control.